JavaScript: The Definitive Guide By David Flanagan - Flanagan, David (O'Reilly Media, 2011)
Since the earliest days of Internet scripting, Web developers have considered JavaScript: The Definitive Guide an essential resource. David Flanagan's approach, which combines tutorials and examples with easy-to-use syntax guides and object references, suits the typical programmer's requirements nicely. The brand-new fourth edition of Flanagan's "Rhino Book" includes coverage of JavaScript 1.5, JScript 5.5, ECMAScript 3, and the Document Object Model (DOM) Level 2 standard from the World Wide Web Consortium (W3C). Interestingly, the author has shifted away from specifying--as he did in earlier editions--what browsers support each bit of the language. Rather than say Netscape 3.0 supports the Image object while Internet Explorer 3.0 does not, he specifies that JavaScript 1.1 and JScript 3.0 support Image. More usefully, he specifies the contents of independent standards like ECMAScript, which encourages scripters to write applications for these standards and browser vendors to support them. As Flanagan says, JavaScript and its related subjects are very complex in their pure forms. It's impossible to keep track of the differences among half a dozen vendors' generally similar implementations. Nonetheless, a lot of examples make reference to specific browsers' capabilities.